Performance of archimedean spiral antenna backed by FSS reflector - Mohamad, Sarah Yasmin; Cahill, Robert; Fusco, Vincent (Institution of Engineering and Technology, 2015)
The use of a backing cavity composed of a frequency selective surface (FSS) above a metal plate as a means to suppress the back lobe radiation and increase the gain of an Archimedean spiral antenna that operates from 3 to 10 GHz is investigated. The FSS is designed to reflect signals in the upper band (7-10 GHz) with a loss of <;0.25 dB, and allow transmission in the lower band (3-6 GHz). Good impedance match and bidirectional to unidirectional beam transformation is obtained when the FSS and metal plate are inserted at a distance λ/4 below the spiral at the centre of the upper and lower bands, respectively. Simulated and measured radiation patterns are employed to show the performance enhancement, which is attributed to the FSS reflector.